Bitterless guaifenesin prodrugs—design, synthesis, characterization, in vitro kinetics, and bitterness studies. (2nd November 2018) - Thawabteh, Amin; Lelario, Filomena; Scrano, Laura; Bufo, Sabino A.; Nowak, Stefanie; Behrens, Maik; Di Pizio, Antonella; Niv, Masha Y.; Karaman, Rafik
Abstract: A respected number of drugs suffer from bitter taste which results in patient incompliance. With the aim of solving the bitterness of guaifenesin, dimethyl maleate, maleate, glutarate, succinate, and dimethyl succinate prodrugs were designed and synthesized. Molecular orbital methods were utilized for the design of the ester prodrugs. The density functional theory (DFT) calculations revealed that the hydrolysis efficiency of the synthesized prodrugs is significantly sensitive to the pattern of substitution on C=C bond and distance between the nucleophile and the electrophile. The hydrolysis of the prodrugs was largely affected by the pH of the medium. The experimental t 1/2 for the hydrolysis of guaifenesin dimaleate ester prodrugs in 1N HCl was the least and for guaifenesin dimethyl succinate was the highest. Functional heterologous expression of TAS2R14, a broadly tuned bitter taste receptor responding to guaifenesin, and experiments using these prodrugs revealed that, while some of the prodrugs still activated the receptor similarly or even stronger than the parent substance, succinate derivatization resulted in the complete loss of receptor responses. The predicted binding modes of guaifenesin and its prodrugs to the TAS2R14 homology model suggest that the decreased activity of the succinate derivatives may be caused by a clash with Phe247. Abstract : A number of novel bitterless ester guaifenesin prodrugs were designed, synthesized, and characterized. The prodrugs have shown sufficient stability at neutral pH values and rapid release under low pH conditions (stomach). Using bitter taste receptor assays, it was confirmed that the most promiscuous human bitter taste receptor responsible for the bitter perception of many drugs, the TAS2R14, is not activated by some of the prodrugs. We conclude that our approach could be used to mask the bitterness of other similar drugs.